Implementasi GPS Tracker pada Sistem Pemesanan Travel berbasis IoT dengan Metode Adaptive Software Development - Prakoso, Anton Bondan; Siswanto, Diky; Istiadi (JASEE Journal of Application and Science on Electrical Engineering, 2025)
High population mobility requires travel services that are fast, transparent, and able to provide reliable vehicle position information. However, many travel service providers still use manual booking and reporting mechanisms, so customer service, data management, and vehicle monitoring are not yet optimal. This study aims to design and implement a web-based travel booking system integrated with real-time vehicle tracking using Internet of Things technology. The system was developed using the Adaptive Software Development method through the stages of speculation, collaboration, and learning. Vehicle position data were acquired using a Global Positioning System NEO6MV2 module connected to a NodeMCU ESP8266 microcontroller, then transmitted to a server through a web-based application programming interface and displayed on the booking dashboard. System testing showed an average data transmission delay of 1.8 seconds, a data delivery success rate of 98%, and coordinate accuracy within ±3–5 meters. These findings indicate that the proposed system can improve booking data management, accelerate vehicle location monitoring, and increase service transparency for users and administrators. In conclusion, the integration of Internet of Things-based tracking and Adaptive Software Development provides an effective approach for developing adaptive, responsive, and integrated telematics applications for travel service operations.